Skincare Branding Strategy: Social Media Marketing, Celebrity Endorsers, and Brand Identity - Angela Evlyn; Handrito, Radityo Putro (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The objective of this quantitative explanatory research is to identify the effects of social media marketing, celebrity endorser, and brand identity on the brand image of Skintific skincare. Using non-probability sampling method and purposive sampling technique, 410 Millennials and Generation Z with the minimum age of 18 years who know about the skincare brand and have accessed information about it, irrespective of whether they purchase the product, were selected as the respondents. The acquired data was analyzed through multiple linear regression in SPSS 29. The results demonstrate that social media marketing does not influence the brand image, that celebrity endorser positively and significantly affects the brand image, and that brand identity positively and significantly influences the brand image.